2018
DOI: 10.1128/mcb.00529-17
|View full text |Cite
|
Sign up to set email alerts
|

Endosomal-Lysosomal Cholesterol Sequestration by U18666A Differentially Regulates Amyloid Precursor Protein (APP) Metabolism in Normal and APP-Overexpressing Cells

Abstract: Amyloid β (Aβ) peptide, derived from amyloid precursor protein (APP), plays a critical role in the development of Alzheimer's disease. Current evidence indicates that altered levels or subcellular distribution of cholesterol can regulate Aβ production and clearance, but it remains unclear how cholesterol sequestration within the endosomal-lysosomal (EL) system can influence APP metabolism. Thus, we evaluated the effects of U18666A, which triggers cholesterol redistribution within the EL system, on mouse N2a ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 109 publications
(184 reference statements)
0
14
0
Order By: Relevance
“…Currently, it is not understood what leads to such a discrepancy. In addition, U18666A, an agent that leads to cholesterol accumulation in endolysosomes, de-acidifies endolysosomes [108], and increases Aβ levels [109]. On the other hand, restoring endolysosomal acidification by GSK3 inhibition [110] or acidic nanoparticle [111113] has been shown to improve amyloid pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, it is not understood what leads to such a discrepancy. In addition, U18666A, an agent that leads to cholesterol accumulation in endolysosomes, de-acidifies endolysosomes [108], and increases Aβ levels [109]. On the other hand, restoring endolysosomal acidification by GSK3 inhibition [110] or acidic nanoparticle [111113] has been shown to improve amyloid pathology.…”
Section: Discussionmentioning
confidence: 99%
“…1C and D). Since cholesterol sequestration enhances APP processing leading to increased secretion of Aβ peptides (Chung et al, 2018;Yang et al, 2017), we wanted to establish if exosomes Disease Models & Mechanisms • DMM • Accepted manuscript derived from UA-treated astrocytes may have a role in the development of AD pathology.…”
Section: Resultsmentioning
confidence: 99%
“…1 C,D). Because cholesterol sequestration enhances APP processing, leading to increased secretion of Aβ peptides ( Chung et al, 2018 ; Yang et al, 2017 ), we wanted to establish whether exosomes derived from U18666A-treated astrocytes may have a role in the development of AD pathology. As a first step, we revealed that exosomes isolated from control astrocytes using polyethylene glycol (PEG)-based precipitation method ( Rider et al, 2016 ) display established exosomal markers flotillin-1, ALIX, TSG101, CD63 and CD81 ( Perez-Gonzalez et al, 2012 ; Raposo and Stoorvogel, 2013 ), but not the negative marker calnexin ( Zhang et al, 2019 ) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations